(untitled) (New York, 1992)
This handbook present a thorough overview of composting as it is practiced on the farm. It explains how to produce, use, and market compost. The information is intended to help farmers decide whether composting or the use of compost is appropriate for their farm. For waste producers, environmental regulators, and provides insight about agricultural composting and what it can reasonably accomplish.
Keywords: Farm,Nông trại